Effectiveness and Safety of Ustekinumab Intensification at 90 mg Every 4 Weeks in Crohn's Disease: A Multicentre Study. (8th September 2020) - Fumery, Mathurin; Peyrin-Biroulet, Laurent; Nancey, Stephane; Altwegg, Romain; Gilletta, Cyrielle; Veyrard, Pauline; Bouguen, Guillaume; Viennot, Stephanie; Poullenot, Florian; Filippi, Jerome; Buisson, Anthony; Bozon, Anne; et al.
Abstract: Background: The approved maintenance regimens for ustekinumab in Crohn's disease [CD] are 90 mg every 8 or 12 weeks. Some patients will respond partially to ustekinumab or will experience a secondary loss of response. It remains poorly known if these patients may benefit from shortening the interval between injections. Methods: All patients with active CD, as defined by Harvey–Bradshaw score ≥ 4 and one objective sign of inflammation [C-reactive protein > 5 mg/L and/or faecal calprotectin > 250 µg/g and/or radiological and/or endoscopic evidence of disease activity] who required ustekinumab dose escalation to 90 mg every 4 weeks for loss of response or incomplete response to ustekinumab 90 mg every 8 weeks were included in this retrospective multicentre cohort study. Results: One hundred patients, with a median age of 35 years [interquartile range, 28–49] and median disease duration of 12 [7–20] years were included. Dose intensification was performed after a median of 5.0 [2.8–9.0] months of ustekinumab treatment and was associated with corticosteroids and immunosuppressants in respectively 29% and 27% of cases. Short-term clinical response and clinical remission were observed in respectively 61% and 31% after a median of 2.4 [1.3–3.0] months. After a median follow-up of 8.2 [5.6–12.4] months, 61% of patients were still treated with ustekinumab, and 26% were in steroid-free clinical remission. Among the 39 patients with colonoscopy during follow-up, 14 achieved endoscopic remission [no ulcers]. At the end of follow-up, 27% of patients were hospitalized, and 19% underwent intestinal resection surgery. Adverse events were reported in 12% of patients, including five serious adverse events. Conclusion: In this multicentre study, two-thirds of patients recaptured response following treatment intensification with ustekinumab 90 mg every 4 weeks.